Preparation method of spherical doped nano-sized iron phosphate and lithium iron phosphate
By using a supergravity reactor in the preparation of lithium iron phosphate combined with particle nanoification, morphology control and in-situ high-valent doping, the problem of low conductivity of lithium iron phosphate and electrons is solved, and a significant improvement in performance and a process suitable for large-scale production is achieved.
Patent Information
- Application Number
- CN202211598163.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The low ion conductivity and electron conductivity of lithium iron phosphate limits its performance under high-rate charging and discharging conditions.
Spherical doped nanoscale lithium iron phosphate is prepared by using a supergravity reactor combined with particle nanoification, morphology control and in-situ high-valent doping method. This method realizes the enhancement of micro-mixture and reaction mass transfer by adjusting the rotation speed and temperature, ensuring the uniform distribution of high-valent doped metal elements and nano-scale particle size.
It significantly improves the ion conductivity and electron conductivity of lithium iron phosphate, improves its performance under high-rate charging and discharge conditions, overcomes the problem of difficult doping of high-valent doped metal salts, and is suitable for large-scale production.
Smart Images

Figure CN115974024B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials for new energy batteries, and specifically relates to a method for preparing spherical doped nano-scale iron phosphate, and also relates to a method for preparing spherical doped nano-scale lithium iron phosphate. Background Art
[0002] Lithium iron phosphate has gradually become a new type of positive electrode material for lithium-ion batteries due to its high theoretical capacity, non-toxicity, and environmental friendliness. However, the lithium ion migration path of olivine-structured lithium iron phosphate is limited to one-dimensional channel diffusion, which makes lithium iron phosphate exhibit low ion conductivity and electronic conductivity at room temperature. It is only suitable for charging and discharging at low current density, and the specific capacity is reduced at high rate charging and discharging. These shortcomings hinder its large-scale application in more fields.
[0003] In order to solve the defects of low ion conductivity and electronic conductivity of lithium iron phosphate, the industry has proposed a variety of modification methods, mainly including: 1) particle nano-crystallization, reducing the particle size of lithium iron phosphate, which can effectively shorten the diffusion path of lithium ions, thereby improving its diffusion rate and improving its rate performance; 2) metal ion doping, after metal ion doping, lattice defects can be created, ion diffusion channels can be widened, and the lithium ion diffusion energy barrier can be reduced. At the same time, the energy gap width can be reduced to a certain extent, and the electronic conductivity of the bulk material can be improved; 3) morphology control, the special morphology structure can make the material and the electrolyte fully contact, Increase the electrochemical active sites of the material, and by controlling the direction of crystal growth, preferentially orient the crystal planes of the lithium ion diffusion channel to ensure rapid insertion of lithium ions and effective conduction of electrons; 4) Carbon coating. The addition of coated carbon will significantly improve the electronic conductivity of the material and improve the charge and discharge performance of the battery at high rates. At the same time, the coated carbon can limit the growth of grains to a certain extent, provide effective electron and ion transmission channels, and the porous structure of the coated carbon can absorb electrolytes. Increasing the contact area with the electrolyte can achieve more electrochemically active sites, thereby continuously outputting excellent and stable electrochemical performance.
[0004] However, the existing modification methods still have limitations in improving the performance of the final product. For example, the second modification method, metal ion doping, the higher the valence of the doped ions, the easier it is to form a large number of holes and distortions in the lattice, making the lithium ion diffusion rate and electronic conductivity better. However, low-valence or equivalent metal ions (such as Mg 2+ 、Co 2+ etc.) doping, doping ions are more likely to replace Fe 2+ The higher the valence (above 3 valence), the harder it is to replace Fe. 2+ Therefore, the conventional doping process does not produce ideal results for high-valent metal ion doping.
[0005] How to further improve the ionic conductivity and electronic conductivity of lithium iron phosphate positive electrode materials is still a research hotspot in the industry, and it is necessary to provide a new method for preparing lithium iron phosphate. Summary of the invention
[0006] To this end, the present invention provides a method for preparing iron phosphate / lithium iron phosphate that can simultaneously achieve particle nano-sizing, morphology control and in-situ high-valent state doping. The ionic conductivity and electronic conductivity of the spherical doped nano lithium iron phosphate positive electrode material finally prepared can be effectively improved.
[0007] First, the present invention provides a method for preparing iron phosphate, comprising the following steps: S11, preparing an iron source, a high-valent doping metal salt and a spherical morphology control agent into a mixed solution; S12, preparing a phosphorus source solution, and respectively using a constant flow pump to flow the phosphorus source solution and the mixed solution into a supergravity reactor at different rates in parallel, adjusting the rotation speed of the supergravity reactor to 1000-2000rpm and the temperature to 60-90°C, and fully reacting to form iron phosphate slurry; S13, separating the iron phosphate slurry into a solid-liquid state, washing, and spray-drying to obtain spherical doped nano-scale iron phosphate.
[0008] Preferably, in step S11, the high-valent doping metal salt is TiCl4, Zr(NO3)4, (NH4) 10 W 12 O 41 、(NH4)2MoO4、C 10 H5B 20 One or more of .
[0009] Preferably, the molar ratio of the metal element in the high-valent doping metal salt to the iron element in the iron source is (0.005-0.05): 1. Preferably, in step S11, the iron source is one or more of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate, ferrous acetate, ferrous citrate, ferrous lactate, and ferrous sulfate; when the iron source is a ferrous source, the mixed solution also includes an oxidant, and the oxidant is hydrogen peroxide or oxygen.
[0010] Preferably, in step S11, the spherical morphology control agent is one or more of ammonium oleate, sodium oleate, polyethylene glycol, polyvinyl pyrrolidone, and 2-hydroxymethylbenzoic acid; the mass ratio of the spherical morphology control agent to the iron source is (0.01-0.2):1.
[0011] Preferably, in step S12, the phosphorus source solution and the mixed solution are added to the supergravity reactor in two stages. In the first stage, the addition rate of the phosphorus source solution is greater than the addition rate of the mixed solution. In the second stage, the addition rate of the phosphorus source solution is less than the addition rate of the mixed solution.
[0012] Preferably, in step S12, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source solution is 1:(0.95-1.15).
[0013] Preferably, in step S12, the phosphorus source solution is prepared from phosphoric acid, sodium hydroxide and pure water, or is prepared from phosphoric acid, ammonia water and deionized water, and the pH of the phosphorus source solution is 1.5-3.0.
[0014] A method for preparing lithium iron phosphate is also provided, comprising the following steps: S10, preparing iron phosphate by the above method;
[0015] S20, mixing the iron phosphate obtained in step S10 with a lithium source and a carbon source, and drying to obtain a spherical lithium iron phosphate precursor; S30, sintering the lithium iron phosphate precursor under a protective atmosphere to obtain nano lithium iron phosphate in situ doped with metal elements.
[0016] Preferably, in step S20, the lithium source is lithium hydroxide or lithium carbonate, and the molar ratio of the iron element in the iron phosphate to the lithium element in the lithium source is 1:(0.5-1.1); the carbon source is 2%-20% of the mass of the iron phosphate, and the carbon source is an organic-inorganic mixture, and the carbon source is a mixture of graphite black and glucose or a mixture of graphene and sucrose.
[0017] The present invention has the following beneficial effects: 1. The present invention utilizes an ultra-gravity reactor and adjusts the rotation speed between 1000 and 2000 rpm, which can generate huge shear force, strengthen the microscopic mixing and reaction mass transfer effect inside the reaction solution, ensure that the concentration is consistent everywhere during the growth and maturation of the crystal nucleus, effectively control the growth and maturation process of the crystal nucleus of the doped iron phosphate precursor, and make the high-valent doping metal element in situ doped in the iron phosphate and evenly distributed, so as to enhance the high-valent doping metal to Fe 2+ The substitution degree and substitution uniformity not only overcome the problem of difficult doping of high-valent metal salts, but also make the prepared iron phosphate have uniform distribution of in-situ high-valent doped metal elements, with a particle size as small as nanometer level and a narrow particle size distribution of 30 to 60 nm.
[0018] 2. In-situ doping of high-valent metal ions improves the smoothness of lithium ion embedding and extraction in the positive electrode material, and enhances the electronic conductivity and lithium ion mobility of lithium iron phosphate.
[0019] 3. The ultra-gravity reactor is used in combination with an organic morphology control agent. During the reaction, the organic agent is more evenly coated on the particle surface, which hinders the particle agglomeration and obtains nano-scale products. At the same time, the doped FePO4·2H2O is controlled to grow into a spherical shape, and the direct contact between particles is hindered to a certain extent during the dehydration and drying process, which effectively inhibits the particle agglomeration and enlargement, and controls the particle size below 60nm, which is suitable for large-scale production.
[0020] 4. Optimize the carbon source coating material, select organic and inorganic carbon sources for composite use, achieve stable and ultra-thin coating while building a three-dimensional conductive network to enhance the surface performance of the material. The organic carbon source can melt and evenly adsorb on the surface of the material particles during the heating stage. Through high-temperature carbonization annealing, the coated carbon layer is tightly attached to the surface of the LiFePO4 particles, forming a three-dimensional conductive network structure; and a small amount of inorganic graphite carbon black or graphene as a supplement to the amorphous carbon to form a conductive network can make the carbon-coated lithium iron phosphate particles connect more fully, thereby forming the best three-dimensional conductive network structure as a whole. This good structure allows good electrical contact between grains and shortens the Li between grain interfaces. + The diffusion distance is shortened, and the rapid transfer of electrons during charging and discharging is promoted.
[0021] 5. The process is suitable for large-scale industrial production and has strong industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an electron microscope image of the iron phosphate obtained in embodiment 1 of the present invention.
[0023] Figure 2 This is an electron microscope image of the lithium iron phosphate obtained in embodiment 1 of the present invention.
[0024] Figure 3 The charge and discharge curves of the lithium iron phosphate prepared in Examples 1 to 3 provided by the present invention. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below through specific implementation methods. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0026] The preparation method of iron phosphate provided by the present invention comprises the following steps: S11, preparing an iron source, a high-valent doping metal salt and a spherical morphology control agent into a mixed solution; S12, preparing a phosphorus source solution, and respectively using a constant flow pump to flow the phosphorus source solution and the mixed solution into a supergravity reactor at different rates in parallel, adjusting the rotation speed of the supergravity reactor to 1000-2000rpm and the temperature to 60-90°C, and fully reacting to form iron phosphate slurry; S13, separating the iron phosphate slurry into a solid-liquid state, washing, and spray-drying to obtain spherical doped nano-scale iron phosphate.
[0027] Wherein, in the step S11, the high-valent doping metal salt is titanium chloride TiCl4, zirconium nitrate Zr(NO3)4, ammonium tungstate (NH4) 10 W 12 O 41 、Ammonium orthomolybdate (NH4)2MoO4、Niobium oxalate C 10 H5B 20 One or more of. The molar ratio of the metal element in the high-valent doped metal salt to the iron element in the iron source is (0.005-0.05):1. The iron source is one or more of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate, ferrous acetate, ferrous citrate, ferrous lactate, and ferrous sulfate; the phosphorus source is ammonium phosphate or sodium phosphate. When the iron source is a ferrous source, the mixed solution also includes an oxidant, and the oxidant is hydrogen peroxide or oxygen.
[0028] The spherical morphology control agent is one or more of ammonium oleate, sodium oleate, polyethylene glycol, polyvinyl pyrrolidone, and 2-hydroxymethylbenzoic acid; the mass ratio of the spherical morphology control agent to the iron source is (0.01-0.2):1.
[0029] In step S12, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source solution is 1:(0.95-1.15). The phosphorus source solution is prepared from phosphoric acid, sodium hydroxide and pure water, or from phosphoric acid, ammonia water and deionized water, and the pH of the phosphorus source solution is 1.5-3.0.
[0030] The phosphorus source solution and the mixed solution are added to the supergravity reactor in two stages. In the first stage, the addition rate of the phosphorus source solution is greater than the addition rate of the mixed solution. In the second stage, the addition rate of the phosphorus source solution is less than the addition rate of the mixed solution. The rotation speed of the supergravity reactor in the first stage is less than that in the second stage.
[0031] The preparation method of lithium iron phosphate provided by the present invention comprises the following steps: S10, preparing iron phosphate by the above method; S20, mixing the iron phosphate obtained in step S10 with a lithium source and a carbon source, and drying to obtain a spherical lithium iron phosphate precursor; S30, sintering the lithium iron phosphate precursor under a protective atmosphere to obtain nano lithium iron phosphate doped with metal elements in situ.
[0032] In step S20, the iron phosphate is mixed with the lithium source and the carbon source by stirring and mixing combined with wet ball milling, and the medium is pure water or ethanol or a combination of the two. The mixed slurry is dried by spray drying, freeze drying, or air drying.
[0033] The lithium source is lithium hydroxide or lithium carbonate, the molar ratio of the iron element in the iron phosphate to the lithium element in the lithium source is 1: (0.5-1.1); the carbon source is 2%-20% of the mass of the iron phosphate, preferably 5%-15%, and the carbon source is an organic-inorganic mixture, such as a mixture of graphite carbon black and glucose or a mixture of graphene and sucrose. Sintering is carried out in a protective atmosphere at 750-900°C, and the sintering time is 8-15h. It can be in a nitrogen atmosphere, an argon atmosphere, or a combination of nitrogen and argon atmosphere.
[0034] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples.
[0035] Example 1
[0036] Step S10, preparing iron phosphate, includes steps S11 to S13.
[0037] Step S11, use a batching tank to prepare a 1 mol / L ferrous sulfate aqueous solution, and add excess oxidant H2O2, TiCl4 (molar ratio is 2% of FeSO4), polyvinyl pyrrolidone and 2-hydroxymethylbenzoic acid (the mass ratio of both is 0.02% of FeSO4) during stirring.
[0038] Step S12, adding phosphoric acid and sodium hydroxide according to the proportion to the deionized water in the phosphorus source batching tank, and adjusting the pH to 1.5-3.0; the solutions prepared in step S11 and step S12 are respectively transported to the supergravity reactor at different rates by constant flow pumps, and the rotation speed (2000 rpm) and the jacket medium temperature (90°C) are adjusted.
[0039] Step S13: the slurry after the reaction is subjected to solid-liquid separation, washing, and spray drying to obtain white spherical titanium-doped ferric phosphate dihydrate powder.
[0040] Step S20, adding the titanium-doped dihydrated iron phosphate powder obtained in step S10 into a stirring tank, adding lithium carbonate and a carbon source, wherein the molar ratio of FePO4:Li2CO3 is 1:0.6, and graphite black and glucose are added at 5% and 10% of the mass of iron phosphate, respectively; using deionized water as the medium, after ball milling, spray drying is used to obtain a spherical lithium iron phosphate precursor.
[0041] Step S30: The lithium iron phosphate precursor powder obtained by the above spraying is sintered in a nitrogen atmosphere furnace at a temperature of 800° C. for 12 hours to obtain nano lithium iron phosphate doped with metal elements.
[0042] Example 2
[0043] Step S10, preparing iron phosphate, includes steps S11 to S13.
[0044] Step S11, use a batching tank to prepare a 1.5 mol / L ferrous sulfate aqueous solution, add Zr(NO3)4 (molar ratio of 3% of FeSO4, polyethylene glycol and ammonium oleate (mass ratio of both of which are 2% of FeSO4), and an excess of hydrogen peroxide aqueous solution (H2O2) during stirring.
[0045] Step S12, adding phosphoric acid and sodium hydroxide according to the proportion to the deionized water in the phosphorus source batching tank, and adjusting the pH to 1.5-3.0; using constant flow pumps to deliver the solutions prepared in step S11 and step S12 to the supergravity reactor at different rates, and adjusting the rotation speed (3000 rpm) and the jacket medium temperature (90°C).
[0046] Step S13: The slurry after the reaction is subjected to solid-liquid separation, washing, and spray drying to obtain white spherical zirconium-doped iron phosphate dihydrate powder.
[0047] Step S20, adding the zirconium-doped dihydrated iron phosphate powder obtained in step S10 into a stirring tank, adding lithium carbonate and a carbon source, wherein the molar ratio of FePO4:Li2CO3 is 1:1, and graphene and sucrose are 2.5% of the mass of iron phosphate respectively; using deionized water as the medium, after ball milling, spray drying is used to obtain a spherical lithium iron phosphate precursor.
[0048] Step S30: The lithium iron phosphate precursor powder obtained by the above spraying is sintered in a nitrogen atmosphere furnace at a temperature of 850° C. for 12 hours to obtain nano lithium iron phosphate doped with metal elements.
[0049] Example 3
[0050] Step S10, preparing iron phosphate, includes steps S11 to S13.
[0051] Step S11: Use a batching tank to prepare a 1.5 mol / L aqueous solution of ferrous sulfate, and add (NH4) during stirring. 10 W 12 O 41 (the molar ratio is 5% of FeSO4), polyethylene glycol and polyvinyl pyrrolidone (the mass ratios of polyethylene glycol and polyvinyl pyrrolidone are both 2% of FeSO4).
[0052] Step S12, adding phosphoric acid and sodium hydroxide according to the proportion to the deionized water in the phosphorus source batching tank, and adjusting the pH to 1.5-2.0; the solutions prepared in step S11 and step S12 are respectively transported to the supergravity reactor at different rates by constant flow pumps, and the rotation speed (3000 rpm) and the jacket medium temperature (90°C) are adjusted.
[0053] Step S13: The slurry after the reaction is subjected to solid-liquid separation, washing, and spray drying to obtain white spherical tungsten-doped iron phosphate dihydrate powder.
[0054] Step S20, adding the tungsten-doped dihydrated iron phosphate powder obtained in step S10 into a stirring tank, adding lithium hydroxide and a carbon source, wherein the molar ratio of FePO4:LiOH is 1:1.2, and graphene and sucrose are 2.5% of the mass of iron phosphate respectively; using deionized water as the medium, after ball milling, spray drying is used to obtain a spherical lithium iron phosphate precursor.
[0055] Step S30: The lithium iron phosphate precursor powder obtained by the above spraying is sintered in a nitrogen atmosphere furnace at a temperature of 880° C. for 12 hours to obtain nano lithium iron phosphate doped with metal elements.
[0056] Table 1 shows the performance data of lithium iron phosphate of Examples 1-3
[0057] project Example 1 Example 2 Example 3 Electronic conductivity of lithium iron phosphate powder (μs / cm) 0.05 0.03 0.04 5C charging capacity (mAh / g) 159.1 159.7 160.0 5C discharge specific capacity (mAh / g) 157.8 158.0 157.6
[0058] The iron phosphate and lithium iron phosphate prepared in Example 1 were tested by electron microscope respectively. Figure 1 and 2 , it can be seen that whether Figure 1 Iron phosphate or Figure 2 The lithium iron phosphate has a small and uniform particle size and is in the form of spherical particles.
[0059] The lithium iron phosphate prepared in Examples 1 to 3 was subjected to charge and discharge tests. Figure 3 ,in Figure 3 Experiments 1, 2 and 3 respectively represent Examples 1, 2 and 3. The lithium iron phosphate prepared by the present invention has a charge specific capacity greater than 159 mAh / g and a discharge specific capacity greater than 157.6 mAh / g.
[0060] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing spherical doped nano-sized iron phosphate, characterized in that: The steps include: S11, preparing a mixed solution of an iron source, a high-valent doping metal salt and a spherical morphology control agent; wherein the high-valent doping metal salt is TiCl4, Zr(NO3)4, (NH4) 10 W 12 O 41 、(NH4)2MoO4、C 10 H5B 20 One or more of; the spherical shape control agent is one or more of ammonium oleate, sodium oleate, polyethylene glycol, polyvinyl pyrrolidone, 2-hydroxymethylbenzoic acid; the mass ratio of the spherical shape control agent to the iron source is (0.01-0.2):1; S12, preparing a phosphorus source solution, and using a constant flow pump to flow the phosphorus source solution and the mixed solution into a high gravity reactor at different rates in parallel, adjusting the rotation speed of the high gravity reactor to 1000-2000 rpm and the temperature to 60-90° C., and fully reacting to form iron phosphate slurry; S13, separating the iron phosphate slurry into solid and liquid, washing, and spray drying to obtain spherical doped nano-scale iron phosphate.
2. The method according to claim 1, characterized in that The molar ratio of the metal element in the high-valent doping metal salt to the iron element in the iron source is (0.005-0.05):
1.
3. The method according to claim 1, characterized in that In step S11, the iron source is one or more of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate, ferrous acetate, ferrous citrate, ferrous lactate, and ferrous sulfate; the phosphorus source is ammonium phosphate or sodium phosphate; when the iron source is a ferrous source, the mixed solution also includes an oxidant, and the oxidant is hydrogen peroxide or oxygen.
4. The method according to claim 1, characterized in that In step S12, the phosphorus source solution and the mixed solution are added to the supergravity reactor in two stages. In the first stage, the addition rate of the phosphorus source solution is greater than the addition rate of the mixed solution. In the second stage, the addition rate of the phosphorus source solution is less than the addition rate of the mixed solution.
5. The method according to claim 1, characterized in that In the step S12, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source solution is 1:(0.95-1.15).
6. The method according to claim 1, characterized in that In step S12, the phosphorus source solution is prepared from phosphoric acid, sodium hydroxide and deionized water, or from phosphoric acid, ammonia water and pure water, and the pH of the phosphorus source solution is 1.5-3.
0.
7. A method for preparing lithium iron phosphate, characterized in that: The steps include: S10, preparing iron phosphate by the method according to any one of claims 1 to 6; S20, mixing the iron phosphate obtained in step S10 with a lithium source and a carbon source, and drying to obtain a spherical lithium iron phosphate precursor; S30, sintering the lithium iron phosphate precursor under a protective atmosphere to obtain nano lithium iron phosphate doped with metal elements in situ.
8. The method according to claim 7, characterized in that In step S20, the lithium source is lithium hydroxide or lithium carbonate, and the molar ratio of the iron element in the iron phosphate to the lithium element in the lithium source is 1: (0.5-1.1); the carbon source is 2%-20% of the mass of the iron phosphate, and the carbon source is an organic-inorganic mixture, and the carbon source is a mixture of graphite black and glucose or a mixture of graphene and sucrose.
Citation Information
Patent Citations
Square monodisperse ferric phosphate and its preparation method
CN102627264A
Lithium-rich manganese-based cathode material precursor, cathode material and preparation method thereof
CN106564967A
Cited By
Preparation method for continuously synthesizing nanoscale sphere-like iron phosphate
CN121085234A